Przedsiębiorcy małego miasta pogranicza polsko-niemieckiego = Private entrepreneurs in a small town of the Polish-German borderland: the case of Krosno Odrzańskie - Mielczarek-Żejmo, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The owners of enterprises in a small town are characterised in two contexts. First, the entrepreneurs` features (age, sex, education, income) are presented against those of other inhabitants of Krosno Odrzańskie - a small town in the Polish-German borderland. Second, differences regarding the characteristics of social position and opinions on transformation among owners of various-size enterprises are presented.
Keywords: pogranicze polsko-niemieckie; Krosno Odrzańskie; przedsiębiorcy; transformacja spoleczna; transformacja ustrojowa